The Use Of Control Suture In Cleft Lip Surgery - Sudjatmiko, Gentur; Ramadan, Mohamad Rachadian (Lingkar Studi Bedah Plastik Foundation, 2012)
To achieve an optimal result in cleft surgery, executing the proper designs and precise techniques are mandatory. Several techniques are proposed for the repair of unilateral and bilateral cleft lip. In 1955, Millard !rst described the techniques of advancing a lateral upper lip